DESIGN OF PROBLEM-BASED LEARNING E-MODULES IN MATHEMATICS TO IMPROVE NUMERACY SKILLS USING CANVA AND HAYZIN - Widayati, Tri (Jurnal Visi Ilmu Pendidikan, 2025)
Abstract The development of problem-based learning e-modules addresses the need for materials to improve mathematical numeracy skills. This research method uses a quantitative method with a problem-based learning model. The e-module prototype was developed using Canva and Hayzine, due to the availability of attractive features and their widespread use. The validity of the problem-based learning e-module was validated by three experts in their respective fields: an educational media expert, a subject matter expert, and a language expert. The key aspects evaluated were readability, interactivity, and curriculum alignment. The results of this validation meet the standards for use as valid instructional materials and demonstrate significant results in improving numeracy skills among elementary school students. The conclusion of this study is that integrating the problem-based learning approach with Canva and Hayzine can create valid electronic modules for improving numeracy skills.